2021
DOI: 10.21203/rs.3.rs-598571/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Paramedic Views of Their Role in Ambulance Based Clinical Trials: An Interview Study

Abstract: Background: Prehospital ambulance-based research is a relatively new and growing field, with paramedics increasingly being asked to take on a new research role. We sought to understand paramedic perceptions of this role with particular emphasis on the ethical challenge of gaining consent and enrolling patients onto clinical trials in this setting. Methods: We undertook semi-structured interviews with paramedics who were actively involved in recruiting and consenting patients to UK trials. Participants were q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The importance of designing pre-hospital trials with minimal paperwork to reduce the participation burden for pre-hospital staff was identified in our study, both directly and indirectly (i.e. limited bandwidth) and has been highlighted in other pre-hospital trials, as well as the logistical challenges related to handover procedures with regards to data collection [1]. Lazarus et al [10] reported that patient enrolment to the PARAMEDIC-2 trial was often constrained by contrasting views and opinions of paramedics who were not involved in the trial.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The importance of designing pre-hospital trials with minimal paperwork to reduce the participation burden for pre-hospital staff was identified in our study, both directly and indirectly (i.e. limited bandwidth) and has been highlighted in other pre-hospital trials, as well as the logistical challenges related to handover procedures with regards to data collection [1]. Lazarus et al [10] reported that patient enrolment to the PARAMEDIC-2 trial was often constrained by contrasting views and opinions of paramedics who were not involved in the trial.…”
Section: Discussionmentioning
confidence: 97%
“…Author details 1 Health Services Research Unit, 3Rd Floor Health Sciences Building, Institute of Applied Health Sciences, School of Medicine, Medical Sciences and Nutrition, University of Aberdeen, Foresterhill, Aberdeen AB25 2ZD, UK. 2 Barts Health NHS Trust, Royal London Hospital, St. Bartholomew's Hospital, London, England.…”
Section: Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have identified factors affecting participation in pre-hospital clinical trials and embedding a culture of research, highlighting the importance of peer communication in recruitment, rather than electronic communication ( Pocock et al, 2019 ). Studies evaluating experiences of and challenges to taking part in pre-hospital research have focused principally on the experiences of paramedics who have recruited patients to clinical trials and the ethical challenges faced ( Ankolekar et al, 2014 ; Armstrong et al, 2021 ; Lazarus et al, 2019 ; Pocock et al, 2019 ). While these studies have similarly identified the high level of motivation of research-active paramedics, there is a clear need for further research exploring barriers to participation among paramedics who are not research active and particularly to understand what might motivate paramedics who are not currently research active to become so.…”
Section: Discussionmentioning
confidence: 99%